The world's great masterpieces of art - Kerrigan, Michael (Flame Tree Publishing, 2015)
The World's Great Masterpieces of Art highlights the most popular art from the beginning of the twelfth century to the Pop Art movement of the twentieth century. With a fresh and thoughtful introduction to the history of art, discussing the work of some of the most famous artists in the world, the book goes on to showcase key works in all their glory.